Statin Treatment in the Acute Phase and the Risk of Post-stroke Pneumonia: A Retrospective Cohort Study - Li, Changling; Ma, Mengmeng; Dong, Shuju; Hong, Ye; Bao, Jiajia; Zhang, Yang; Gao, Lijie; Cui, Chaohua; Guo, Jian; He, Li (Frontiers in Neurology, 2021)
Background: We aimed to investigate the impact of statin treatment in the acute phase on the risk and severity of post-stroke pneumonia because of the uncertain effects of statins on post-stroke pneumonia. Methods: Consecutive cases of acute ischemic stroke (AIS) between January 2014 and February 2019 were retrospectively analyzed. Additionally, the association of statin treatment in the acute phase with the risk and severity of post-stroke pneumonia was estimated with logistic regression. We registered the present study in the Chinese Clinical Trial Registry (ChiCTR 2000032838). Results: Of the 1,258 enrolled patients, no significant difference was observed in post-stroke pneumonia risk between the two groups (with/without statin treatment in the acute phase) after propensity score matching (35.1 vs. 27.9%, p = 0.155). We did not find statin treatment in the acute phase to significantly increase the risk of post-stroke pneumonia both before and after matched analysis [odds ratio (OR) = 1.51, 95% confidence interval (CI) = 0.85–2.67, p = 0.157; OR = 1.57, 95% CI = 0.77–3.18, p = 0.213, respectively]. In the 271 patients with post-stroke pneumonia, no significant difference was found in its severity between two groups (19.6 vs. 19.4%, p = 0.964). No significant association was found between statin treatment and post-stroke pneumonia severity (OR = 0.95, 95% CI = 0.39–2.31, p = 0.918). Conclusions: There appeared to be no additional benefits of statin treatment in the acute phase for post-stroke pneumonia reduction among AIS patients. Clinical Trial Registration:http://www.chictr.org.cn, identifier: ChiCTR2000032838.